Initial Airworthiness Determining the Acceptability of New Airborne Systems - Gratton, Guy (Springer International Publishing, 2018)
Designed as an introduction for both advanced students in aerospace engineering and existing aerospace engineers, this book covers both engineering theory and professional practice in establishing the airworthiness of new and modified aircraft. Initial Airworthiness includes information on: · how structural, handling, and systems evaluations are carried out; · the processes by which safety and fitness for purpose are determined; and · the use of both US and European unit systems Covering both civil and military practice and the current regulations and standards across Europe and North America, Initial Airworthiness will give the reader an understanding of how all the major aspects of an aircraft are certified, as well as providing a valuable source of reference for existing practitioners. This second edition has been updated for changes in regulation worldwide, including UK "E-conditions" and Single Seat De-Regulation, the new part 23 regulations in the USA and Europe, and developments to Extended Range Twin-Engine Operations worldwide. Entirely new sections have been added to explain the management of certification programmes, professional ethics within airworthiness practice, environmental impact of aircraft, and aeroplane departures from controlled flight. This edition also includes many new figures, case studies and references to sources of further information.